The paradox of rhetorical structures In the poetry of Walid Al-Sarraf - العنبكي, ساهرة عدنان وهيب (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Rhetorical paradox is of interest to scholars in the rhetorical and critical fields, as it is a creative culture that indicates the skills of poets in their artistic and aesthetic preparations, and the poet is the one who employs those mechanisms that achieve the poetics of the text and its literary uniqueness in the midst of grammatical, rhetorical, and critical studies. We focus the research on paradox in rhetorical structures, sentence grammar, and related matters. With the knowledge of meanings, it investigates the creative influence that influences the recipient from the vertical poetic texts in the modernist poem, if we know that the poet is one of the poets of the poetic column. Despite the presence of some free texts, his collections are vertical with distinction. Irony in the rhetorical structure carries semantic and intellectual implications with its past emotional outbursts and twists that dazzle the reader and lure him into creative participation with the poem’s loads of astonishment, astonishment, alienation, astonishment, breaking of expectation, surprise, impression, surrender or acquiescence, from a significance that can be deduced fro m the sarcastic, sarcastic, dazzling, or rebellious text. Or the critic, through many transformations in the grammatical context and compositional format, which indicates the recipient to search for artistic and aesthetic value.